Comparative genomics of Pseudomonas fluorescens subclade III strains from human lungs. (December 2015) - Scales, Brittan; Erb-Downward, John; Huffnagle, Ian; LiPuma, John; Huffnagle, Gary
Abstract Background While the taxonomy and genomics of environmental strains from theP. fluorescens species-complex has been reported, little is known aboutP. fluorescens strains from clinical samples. In this report, we provide the first genomic analysis ofP. fluorescens strains in which human vs. environmental isolates are compared. Results SevenP. fluorescens strains were isolated from respiratory samples from cystic fibrosis (CF) patients. The clinical strains could grow at a higher temperature (>34 °C) than has been reported for environmental strains. Draft genomes were generated for all of the clinical strains, and multi-locus sequence analysis placed them within subclade III of theP. fluorescens species-complex. All strains encoded type- II, −III, −IV, and -VI secretion systems, as well as the widespread colonization island (WCI). This is the first description of a WCI inP. fluorescens strains. All strains also encoded a complete I2/PfiT locus and showed evidence of horizontal gene transfer. The clinical strains were found to differ from the environmental strains in the number of genes involved in metal resistance, which may be a possible adaptation to chronic antibiotic exposure in the CF lung. Conclusions This is the largest comparative genomics analysis ofP. fluorescens subclade III strains to date and includes the first clinical isolates. At a global level, the clinicalP. fluorescens subclade III strains were largely indistinguishable from environmentalP. fluorescens subclade III strains, supporting the idea that identifying strains as 'environmental' vs 'clinical' is not a phenotypic trait. Rather, strains withinP. fluorescens subclade III will colonize and persist in any niche that provides the requirements necessary for growth.